Knowledge and behaviors of Turkish dentists regarding rational drug use in pediatric patients: a cross-sectional survey - Menekşe Alim; Nurhan Öztaş Kirmizi (BMC Oral Health)
Abstract Background Medication use is a highly sensitive issue, especially in children, as they have different physiology than adults. Assessing the accuracy and awareness of drug prescribing practices of dentists, who play an important role in drug use, is critical for developing effective health policies and professional education programs. Therefore, the aim of this study was to evaluate the knowledge and behaviors of dentists caring for pediatric patients regarding rational drug use and the factors associated with these behaviors. Materials and methods In this cross-sectional study, the sample consisted of 260 Turkish dentists. Participants included general dentists, pediatric dentists and pediatric dentistry residency students. A special questionnaire was developed for data collection. The first part of the questionnaire consisted of sociodemographic data, the second part of the questionnaire consisted of questions about the status and desire for rational drug use education, and the third part of the questionnaire consisted of multiple-choice questions assessing the dentists’ knowledge and behaviors related to rational drug use. The 6 multiple-choice questions determined to evaluate the level of knowledge had one or more correct answers and each correct answer was accepted as 1 point. A scoring system with a total of 20 points was developed with the correct answers given to these questions. Results General dentists scored the lowest in knowledge (mean = 11.71), while pediatric dentistry residents scored the highest (mean = 14.38), (p < 0.05). Knowledge level was not statistically associated with receiving rational drug use training (p > 0.05). The knowledge level of the participants with a professional experience of 10 years or more was found to be lower than those with less experience (p < 0.05). Conclusion This study reveals a lack of knowledge on rational drug use, especially among general dentists and dentists with more than 10 years of professional experience. This finding clearly shows that the scope of educational programs should be expanded and post-graduation training should be provided to ensure retention of knowledge. Clinical trial number Not applicable.